(R)-[(R)-3-Benzyl-2-oxooxazolidin-4-yl][4-(methylsulfonyl)phenyl]methyl acetate - Li, Feng (International Union of Crystallography, 2014)
The structure of the title compound, C(20)H(21)NO(6)S, is of interest with respect to its antibacterial properties. The oxazolidine ring makes dihedral angles of 79.63 (14) and 56.16 (12)° with the phenyl and benzene rings, respectively, while the phenyl and benzene rings make a dihedral angle of 64.37 (13)°. In the crystal, non-classical C—H⋯O hydrogen bonds link adjacent molecules along the c axis.